Revealing the Importance of Iron Aerogel Features as Electrocatalysts for the Oxygen Reduction Reaction - Judith González-Lavín; Ana Arenillas; Natalia Rey-Raap (Gels)
Metal nanoparticles supported in carbon materials are the traditional electrocatalyst currently used in many applications. However, these composite materials have many problems associated with the optimization of both components for the specific application, besides the stability of the mixture. Self-supported metallic materials may be an interesting strategy in order to avoid the traditional carbon supports; however, these metallic materials should present highly active surface area. Iron aerogels are presented in this work as effective and affordable unsupported electrocatalysts. The combination of their metallic structure with high porosity (i.e., 85 m2 g−1 and 0.45 cm3 g−1 of mesopore volume), due to their interconnected tridimensional structure, leads to a great activity versus the oxygen reduction reaction. A method for producing iron aerogels based on microwave-assisted sol–gel methodology is presented. The incorporation of carbon functionalities to the iron aerogels seems to clearly influence the mechanism of the reaction, favoring the direct mechanism of the oxygen reduction reaction and thus notably improving the performance of the electrocatalysts. Chemical vapor deposition seems to be an adequate methodology for incorporating carbon functionalities to the transition metal structure without affecting the tridimensional network and leading to current densities over 4 mA cm−2 and great stability even after 10,000 s.